2018
DOI: 10.1017/inp.2018.18
|View full text |Cite
|
Sign up to set email alerts
|

Vegetative Community Response to Landscape-Scale Post-fire Herbicide (Imazapic) Application

Abstract: Disturbances such as wildfire create time-sensitive windows of opportunity for invasive plant treatment, and the timing of herbicide application relative to the time course of plant community development following fire can strongly influence herbicide effectiveness. We evaluated the effect of herbicide (imazapic) applied in the first winter or second fall after the 113,000 ha Soda wildfire on the target exotic annual grasses and also key non-target components of the plant community. We measured responses of ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 46 publications
4
24
1
Order By: Relevance
“…Based on previous laboratory and experimental studies (Meyer et al., 2010, 2016), we expected head smut induced reductions in seed and correspondingly less cheatgrass in subsequent years, which would be a mechanism of negative density dependence. While we found reductions in cheatgrass cover associated with higher perennial bunchgrass and herbicide application in agreement with findings from previous research (Applestein et al., 2018; Germino et al., 2019), higher smut infection did not correlate with lower cheatgrass cover the following year. In contrast, smut infection was positively correlated with prior year cheatgrass cover, suggesting that host density may influence disease severity more strongly than the subsequent reciprocal impact of smut on these invasive annual grass populations.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Based on previous laboratory and experimental studies (Meyer et al., 2010, 2016), we expected head smut induced reductions in seed and correspondingly less cheatgrass in subsequent years, which would be a mechanism of negative density dependence. While we found reductions in cheatgrass cover associated with higher perennial bunchgrass and herbicide application in agreement with findings from previous research (Applestein et al., 2018; Germino et al., 2019), higher smut infection did not correlate with lower cheatgrass cover the following year. In contrast, smut infection was positively correlated with prior year cheatgrass cover, suggesting that host density may influence disease severity more strongly than the subsequent reciprocal impact of smut on these invasive annual grass populations.…”
Section: Discussionsupporting
confidence: 92%
“…While stand‐level epidemics and subsequent cheatgrass stand failure have been documented in some infrequent previous instances (Meyer et al., 2010, 2016), we did not observe any such events during the first 4 years post‐fire in our study system in or around the plots reported here or elsewhere in the region (>2,500 plots sampled in Germino et al., 2018, 2019; Applestein et al., 2018, or Davidson & Germino, 2020). Fewer than half of all cheatgrass individuals were infected in the majority of plots and fewer than 17% plots contained the highest infection levels (>75% of plants), across all years (Table 2).…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…Some studies have compared invasive annual grass control by herbicide (Applestein, Germino, & Fisk, 2018; Clements, Harmon, Blank, & Weltz, 2017; Elseroad & Rudd, 2011; Sebastian, Nissen, Sebastian, Meiman, & Beck, 2017b), but few have examined potential ways to control invasive annual grasses while simultaneously allowing seeding of native species that are also susceptible to herbicide (Clark, Sebastian, Nissen, & Sebastian, 2020; Eckert et al., 1974). Here we study two herbicides that differ in mode of action, soil persistence, and soil mobility to identify potential strategies that control invasive grasses without harming native species seeded for restoration.…”
Section: Introductionmentioning
confidence: 99%
“…Management treatments that focus specifically on exotic annual grasses include pre‐emergent herbicides such as imazapic, which inhibit germination and thereby create selective disadvantages for annuals such as EAGs compared to perennial species (e.g., Kyser et al, 2013; Davies et al, 2014). Imazapic can also cause some post‐emergent reduction in EAG growth (Mangold et al, 2013; Applestein et al, 2018). Weed‐suppressive bacteria (strains of Pseudomonas fluorescens ) have also emerged as a potential tool for specifically targeting particular EAGs (Kennedy et al, 1991; Kennedy, 2018), though they have not been consistently effective in field trials to date (reviewed in Germino & Lazarus, 2020).…”
Section: Introductionmentioning
confidence: 99%